Self-regulated learning of alternative learning system senior high school learners in flexible learning modality - Hero, Jesson L.; Gloria, Daianne S. (Intelektual Pustaka Media Utama, 2025)
The alternative learning system senior high school (ALS SHS) practiced flexible learning as its learning modality to give more opportunities and convenience making the program more inclusive and responsive to learners’ needs. It also ensures that learners adhere to instructional competence and self-regulated learning (SRL). However, there is a lack of evidence under the program about the dissection of SRL. Hence, this sequential explanatory mixed method research aimed to evaluate SRL vis-à-vis the weaknesses and challenges encountered by ALS SHS learners enrolled in one public senior high school (SHS) in the City of Meycauayan, Bulacan. The findings showed that most respondents were early and middle adults, female, and currently working and demonstrated an observable SRL. There is a significant difference in SRL among learners when the profile is considered. The challenges encountered are focused on strategic academic planning and goal setting, preparedness and awareness in SRL, and support groups. The proposed capacity-building program aimed to offset the challenges encountered and improve the SRL of ALS SHS learners. Furthermore, this study affirmed the goodness-of-fit between the context of the research and the theory of SRL in improving the SRL of ALS SHS learners.